2005
DOI: 10.1152/japplphysiol.01139.2004
|View full text |Cite
|
Sign up to set email alerts
|

ACTN3 genotype is associated with increases in muscle strength in response to resistance training in women

Abstract: The alpha-actinin 3 (ACTN3) gene encodes a protein of the Z disk of myofibers, and a polymorphism of ACTN3 results in complete loss of the protein. The ACTN3 genotype (R577X) has been found to be associated with performance in Australian elite athletes (Yang N, MacArthur DG, Gulbin JP, Hahn AG, Beggs AH, Easteal S, and North K. Am J Hum Genet 73: 627-631, 2003). We studied associations between ACTN3 genotype and muscle size [cross-sectional area of the biceps brachii via magnetic resonance imaging (MRI)] and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
232
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 269 publications
(256 citation statements)
references
References 28 publications
15
232
1
2
Order By: Relevance
“…Approximately 20% of the world population, and 18% of the European population, harbour the ACTN3 577XX genotype and consequently are completely deficient in ␣-actinin-3. 3 The ACTN3 R577X polymorphism has been investigated in the context of human athletic performance, in both elite endurance and power athletes, [4][5][6] and the general population, [7][8][9] with the overall conclusion that ␣-actinin-3 deficiency, as marked by the 577XX genotype, is detrimental to power performance and possibly beneficial to endurance performance. Recently, we have shown, in a large group of elite European athletes (n = 633), that 'worldclass' endurance athletes were 3.7 times more likely to harbour the 577XX genotype than national-level counterparts, and that elite power athletes were ∼50% less likely to harbour the 577XX genotype compared to sedentary controls.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% of the world population, and 18% of the European population, harbour the ACTN3 577XX genotype and consequently are completely deficient in ␣-actinin-3. 3 The ACTN3 R577X polymorphism has been investigated in the context of human athletic performance, in both elite endurance and power athletes, [4][5][6] and the general population, [7][8][9] with the overall conclusion that ␣-actinin-3 deficiency, as marked by the 577XX genotype, is detrimental to power performance and possibly beneficial to endurance performance. Recently, we have shown, in a large group of elite European athletes (n = 633), that 'worldclass' endurance athletes were 3.7 times more likely to harbour the 577XX genotype than national-level counterparts, and that elite power athletes were ∼50% less likely to harbour the 577XX genotype compared to sedentary controls.…”
Section: Introductionmentioning
confidence: 99%
“…Massidda et al [42] have reported that the ACTN3 R577X genotype accounts for 8.0% of the variation in squat-jump performance of elite soccer players. In the general population, the ACTN3 R577X polymorphism is responsible for 1-2% of the variation in muscle strength [37,43]. These results suggest that the ACTN3 R577X genotype has an apparent contributing role in competitive athletes, particularly elite athletes compared to that in the general population.…”
Section: Effect Of Actn3 R577x Polymorphism On Athletic Performance Amentioning
confidence: 92%
“…The experimental design of FAMuSS has been described elsewhere [6,[15][16][17][18][19][20][21]. The institutional review boards from the 10 institutions involved with the study approved the study protocol and informed consent was obtained from all individuals prior to enrollment.…”
Section: Methodsmentioning
confidence: 99%